Ultrsonic testing of bond integrity in adhesive joints between 2 similar metals - Ang, Marcus (2017)
Non-destructive testing (NDT) involves a wide variety of analytical techniques to evaluate properties of material without causing damage. In this project, the aluminium test specimens are designed closely in accordance to the American Society for Testing and Materials (ASTM) D1002 standard. The epoxy adhesive will be used at the lap-joint of the specimens. Different adhesive composition will be applied at the joint for each specimen. The A-scan will be used as ultrasonic testing at the overlap region of the lap-joint. Firstly, attenuation loss is calculated based on the 1st back-echo (B.E) and 2nd B.E readings obtained from the experiment. The result shows that higher attenuation loss is present at specimens with fully cured adhesive compared to uncured adhesive or water. It is also observed that the screen height amplitude of the 1st B.E varies with the corresponding composition of adhesive applied at the lap-joint. When the adhesive is fully cured and solidified, the 1st B.E amplitude is lower whereas the 1st B.E amplitude is much higher when the adhesive is uncured. In the presence of a cohesive bond at the adhesive-adherend interface, the A-scan is able to pick up the adhesive signals during ultrasonic testing. While in the presence of a disbond, the A-scan is unable to pick up the signals. Lastly the specimens with fully cured adhesive are subjected to the instron lap-joint shear test. The maximum load of the specimen will be determined at the point of fracture at the lap-joint. However, this technique is insufficient in determining the bond quality of the adhesive from the results obtained. Even though A-scan has shown reliable results in detecting the presence of disbond, further studies on different analytical techniques are necessary to characterise the bond quality between two similar metals.